You should remember that `cot x = cos x/sin x,` hence, you may write the integrand such that:

`int (cos x/sin x)ln(sin x)dx`

You should come pu with the following substitution such that:

`sin x = t => cos x dx = dt`

Changing the variable yields:

`int (cos x/sin x)ln(sin x)dx = int (ln t)/t dt`

You should use the next substitution such that:

`ln t = u => 1/t dt = du`

`int (ln t)/t dt = int udu`

`int udu = u^2/2 + c`

Substituting back `ln t` for u yields:

`int (ln t)/t dt = (ln^2 t)/2 + c`

Substituting back `sin x` for t yields:

`int (cos x/sin x)ln(sin x)dx = (ln^2 (sin x))/2 + c`

**Hence, evaluating the given integral using substitution yields `int (cos x/sin x)ln(sin x)dx = (ln^2 (sin x))/2 + c.` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now